2017
DOI: 10.1097/jcn.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Depression, and Anxiety in Ventricular Assist Device Therapy

Abstract: Background: Patients who receive ventricular assist device (VAD) therapy typically rely on informal caregivers (family members or friends) to assist them in managing their device. Objective: The purpose of this study is to characterize changes in person-oriented outcomes (quality of life [QOL], depression, and anxiety) for VAD patients and their caregivers together from pre-implantation to 3 months post-implantation. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 45 publications
3
51
1
Order By: Relevance
“…This was a prospective longitudinal study of patients receiving an LVAD and their caregivers (n=50 dyads, where each dyad consists of a patient and associated caregiver). 14,15 Because little research has been done to examine patient-caregiver dyads in LVAD therapy, no formal sample size calculation based on expected effect sizes was conducted; rather, sample size was primarily determined by the number of patients and caregivers it was feasible to enroll during the funding period on the basis of center implantation rates. In short, patients were eligible for enrollment if they were ≥21 years of age, eligible to receive an LVAD, and without previous heart transplantation.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…This was a prospective longitudinal study of patients receiving an LVAD and their caregivers (n=50 dyads, where each dyad consists of a patient and associated caregiver). 14,15 Because little research has been done to examine patient-caregiver dyads in LVAD therapy, no formal sample size calculation based on expected effect sizes was conducted; rather, sample size was primarily determined by the number of patients and caregivers it was feasible to enroll during the funding period on the basis of center implantation rates. In short, patients were eligible for enrollment if they were ≥21 years of age, eligible to receive an LVAD, and without previous heart transplantation.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Perhaps more significant is the inverse relationship between context (e.g., anxiety) and distal outcome (QOL) dimensions. This finding can be explained by the fact that anxiety and depression are highly prevalent in the LVAD population (29,30). As shown in Table 3, our study patients' anxiety and depression scores were slightly worse than the average score of U.S. adults living with the same condition (anxiety and depression; (18)).…”
Section: Discussionmentioning
confidence: 57%
“…As shown in Table 3, our study patients' anxiety and depression scores were slightly worse than the average score of U.S. adults living with the same condition (anxiety and depression; (18)). Remarkably, the coexistence of anxiety and depression, and associated negative influences on QOL, are commonly reported in heart failure studies and from data derived from the LVAD population (29)(30)(31).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…patients with a diagnosis of depression and of both depression and anxiety (9). Caregivers, on their part, are constantly exposed to psychological burden and it is known that their emotional distress can influence patients themselves (6,7). Bruce et al (10) demonstrated that the presence of prepared and efficient caregivers significantly reduces the risk of mortality in LVAD patients.…”
mentioning
confidence: 99%